Is a field-induced ferromagnetic phase transition in the magnetar core actually possible? - Isayev, А.А.; Yang, J. (Вопросы атомной науки и техники, 2012)
Spin polarized states in dense neutron matter with BSk20 Skyrme force are considered in magnetic fields up to 10²⁰ G. It is shown that the appearance of the longitudinal instability in a strong magnetic field prevents the formation of a fully spin polarized state in neutron matter, and only the states with moderate spin polarization can be developed. Рассматриваются спиновоупорядоченые состояния в плотной нейтронной материи с силой Скрима BSk20 в магнитных полях вплоть до 10²⁰ Гс. Показано, что появление продольной неустойчивости в сильном поле препятствует формированию полностью поляризованного состояния и возможны только состояния с умеренной поляризацией. Розглядаються спінововпорядковані стани в густій нейтронній матерії з силою Скірма BSk20 в магнітних полях до 10²⁰ Гс. Показане, що поява поздовжньої нестійкості в сильному магнітному полі перешкоджає формуванню повністю поляризованого стану і можливі тільки стани з помірною поляризацією.